2019
DOI: 10.5713/ajas.18.0792
|View full text |Cite
|
Sign up to set email alerts
|

Effects on microbial diversity of fermentation temperature (10°C and 20°C), long-term storage at 5°C, and subsequent warming of corn silage

Abstract: Objective To evaluate the effects on microbial diversity and biochemical parameters of gradually increasing temperatures, from 5°C to 25°C on corn silage which was previously fermented at ambient or low temperature. Methods Whole-plant corn silage was fermented in vacuum bag mini-silos at either 10°C or 20°C for two months and stored at 5°C for two months. The mini-silos were then subjected to additional incubation from 5°C to 25°C in 5°C increments. Bacterial and funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…The normal storage temperature (25 • C) might be a good temperature for higher LAB activity during the earlier fermentation process in silage, as reflected by the higher LA and lower pH in NT treatments (Table 2). Previous studies also revealed similar results regarding the effect of storage temperature on the fermentation characteristics of whole-plant corn silage (Zhou et al, 2016(Zhou et al, , 2019Ferrero et al, 2021). However, the LAB in the final silage might be inhibited by the low pH condition (McDonald et al, 1991), which resulted in lower LAB count in NT treatments (Table 3).…”
Section: Materials Characteristics and Silage Qualitysupporting
confidence: 67%
“…The normal storage temperature (25 • C) might be a good temperature for higher LAB activity during the earlier fermentation process in silage, as reflected by the higher LA and lower pH in NT treatments (Table 2). Previous studies also revealed similar results regarding the effect of storage temperature on the fermentation characteristics of whole-plant corn silage (Zhou et al, 2016(Zhou et al, , 2019Ferrero et al, 2021). However, the LAB in the final silage might be inhibited by the low pH condition (McDonald et al, 1991), which resulted in lower LAB count in NT treatments (Table 3).…”
Section: Materials Characteristics and Silage Qualitysupporting
confidence: 67%
“…However, the length of the fermentation period and incubation temperature differed in the two studies, and in the former study, the bag silos were stored outside. Considering the lower average temperatures encountered during the incubation of the bag silos, we would expect microbial succession to be slower than in mini‐silos stored at room temperature (Zhou et al, 2019). The presence of Leuconostocaceae at this late stage of ensiling is rare in corn silage, considering that upon the opening of the bag silos, pH was below 4.0, a pH to which species belonging to this family are sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The cubic model (Y = a + bx + cx 2 + dx 3 ) was the one that presented the best fit for the evaluation of the temperature behavior (Table 2, Figure 1) and pH (Table 3, Figure 2) of the cocoa shell SSF. However, Zhou et al (2019) mention that temperatures between 20 and 25 °C, guarantees the growth of lactic acid bacteria colonies such as Lactobacillus buchneri, these favors a rapid increase in the concentration of lactic acid, and the rapid decrease in pH to favor the silage process (Muck 2013;Wang et al 2017;Caicedo et al 2019b), in this study the cocoa shell SSF remained within the optimum temperature ranges for the production of good quality silage. On the other hand, temperatures below 10 °C or above 37 °C affect the fermentation process, leading to poor quality silage and low aerobic stability (Zhou et al 2019;Bernardes et al 2018).…”
Section: Resultsmentioning
confidence: 53%
“…However, Zhou et al (2019) mention that temperatures between 20 and 25 °C, guarantees the growth of lactic acid bacteria colonies such as Lactobacillus buchneri, these favors a rapid increase in the concentration of lactic acid, and the rapid decrease in pH to favor the silage process (Muck 2013;Wang et al 2017;Caicedo et al 2019b), in this study the cocoa shell SSF remained within the optimum temperature ranges for the production of good quality silage. On the other hand, temperatures below 10 °C or above 37 °C affect the fermentation process, leading to poor quality silage and low aerobic stability (Zhou et al 2019;Bernardes et al 2018). On the other hand, immediately after the fermentation of the raw material, a variation in pH occurs, which reaches values between 5.5 and 6 due to the low concentration of lactic, acetic and propionic acid in the medium (Kung et al 2018).…”
Section: Resultsmentioning
confidence: 53%